Maternal risk factors of urinary incontinence during pregnancy and postpartum: A prospective cohort study. (January 2022) - Rajavuori, Anna; Repo, Jussi P.; Häkkinen, Arja; Palonen, Pirkko; Multanen, Juhani; Aukee, Pauliina
Highlights: Urinary incontinence after delivery affects every fifth woman. Urinary incontinence before pregnancy is a risk factor of postpartum incontinence. Primiparous women are at a greater risk of urinary incontinence after birth. Abstract: Introduction: Urinary incontinence (UI) during pregnancy is a common health problem. Vaginal delivery in particular affects the pelvic floor and increases the risk of pelvic floor dysfunctions. This prospective cohort study was conducted to investigate the incidence of UI during pregnancy and three months postpartum and determine the risk factors underlying UI. Methods: In total, 547 volunteer women were recruited from the maternity clinic of a tertiary hospital. The participants filled out a questionnaire twice, one in the second trimester and the other three months after delivery. A multivariate logistic regression model with forward stepwise selection was used to analyze known risk factors for UI. Results: The prevalence of UI during pregnancy was 39.5% and three months after childbirth 16.1%. Twenty-two percent of participants had pre-existing UI compared to 41.0% of the 88 women with UI three months postpartum. UI before pregnancy (OR 2.2), during pregnancy (OR 3.8) and primiparity (OR 2.3) were significantly associated with postpartum UI. Conclusions: Women with UI before or during pregnancy and who are primiparous are at increased risk for postpartum UI. To prevent and reduce the risk factors contributing to UI, pregnant women should be routinely counseled.